An Enzybiotic Regimen for the Treatment of Methicillin-Resistant Staphylococcus aureus Orthopaedic Device-Related Infection - Eric T. Sumrall; Marloes I. Hofstee; Daniel Arens; Christian Röhrig; Susanne Baertl; Dominic Gehweiler; Mathias Schmelcher; Martin J. Loessner; Stephan Zeiter; R. Geoff Richards; T. Fintan Moriarty (MDPI AG, 2021)
Orthopaedic device-related infection (ODRI) presents a significant challenge to the field of orthopaedic and trauma surgery. Despite extensive treatment involving surgical debridement and prolonged antibiotic therapy, outcomes remain poor. This is largely due to the unique abilities of Staphylococcus aureus, the most common causative agent of ODRI, to establish and protect itself within the host by forming biofilms on implanted devices and staphylococcal abscess communities (SACs). There is a need for novel antimicrobials that can readily target such features. Enzybiotics are a class of antimicrobial enzymes derived from bacteria and bacteriophages, which function by enzymatically degrading bacterial polymers essential to bacterial survival or biofilm formation. Here, we apply an enzybiotic-based combination regimen to a set of in vitro models as well as in a murine ODRI model to evaluate their usefulness in eradicating established S. aureus infection, compared to classical antibiotics. We show that two chimeric endolysins previously selected for their functional efficacy in human serum in combination with a polysaccharide depolymerase reduce bacterial CFU numbers 10,000-fold in a peg model and in an implant model of biofilm. The enzyme combination also completely eradicates S. aureus in a SAC in vitro model where classical antibiotics are ineffective. In an in vivo ODRI model in mice, the antibiofilm effects of this enzyme regimen are further enhanced when combined with a classical gentamicin/vancomycin treatment. In a mouse model of methicillin-resistant S. aureus (MRSA) ODRI following a fracture repair, a combined local enzybiotic/antibiotic treatment regimen showed a significant CFU reduction in the device and the surrounding soft tissue, as well as significant prevention of weight loss. These outcomes were superior to treatment with antibiotics alone. Overall, this study demonstrates that the addition of enzybiotics, which are distinguished by their extremely rapid killing efficacy and antibiofilm activities, can enhance the treatment of severe MRSA ODRI.